2015
DOI: 10.12775/qs.2015.018
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem and the value of body in people who exercise regularly at the gym - the results of pilot studies

Abstract: Poczucie własnej wartości oraz wartości własnego ciała u osób ćwiczących regularnie na siłowni-wyniki badań pilotażowych Self-esteem and the value of body in people who exercise regularly at the gymthe results of pilot studies Streszczenie Wstęp. Ćwiczenie na siłowni staje się coraz bardziej popularne, zarówno wśród kobiet, jak i wśród mężczyzn. Regularne treningi, poza zmianami morfologicznymi oraz funkcjonalnymi mogą mieć wpływ na zmiany pewnych aspektów psychologicznych, szczególnie dotyczących poczucia wła… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…These results are in line with previous studies in which individuals who engage in regular physical exercise possess a realistic appraisal of their physical bodies [51]. Also in a study by Ziemianek et al [50], in which the authors examined the self-esteem and body image of women and men who exercise at the gym, the outcomes from the BES questionnaire show that physically active people rate their bodies above average. The obtained results are also in line with previous research in which athletes demonstrated enhanced confidence through the use of imagery for this objective [43].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are in line with previous studies in which individuals who engage in regular physical exercise possess a realistic appraisal of their physical bodies [51]. Also in a study by Ziemianek et al [50], in which the authors examined the self-esteem and body image of women and men who exercise at the gym, the outcomes from the BES questionnaire show that physically active people rate their bodies above average. The obtained results are also in line with previous research in which athletes demonstrated enhanced confidence through the use of imagery for this objective [43].…”
Section: Discussionsupporting
confidence: 90%
“…A study by Ziemianek et al [50], in which the authors examined the self-esteem and body image of women and men who exercise at the gym, showed that physically active people rate their bodies above average. In a study by Budnik-Przybylska et al [51], dancers showed higher imagery abilities as well as better ratings of their bodies in terms of physical fitness.…”
mentioning
confidence: 99%
“…In a study by Ziemianek et al [46], in which they examined the self-esteem and body image of women and men who exercise at the gym, results from the BES questionnaire show that physically active people rate their bodies above average. The above results are also consistent with a study by Budnik-Przybylska et al [47], in which dancers showed higher imagery abilities as well as better ratings of their bodies in terms of physical fitness.…”
Section: Discussionmentioning
confidence: 99%